2008
DOI: 10.1523/jneurosci.5595-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Bötzinger Expiratory-Augmenting Neurons and the Parafacial Respiratory Group

Abstract: In neonatal rat brains in vitro, the rostral ventral respiratory column (rVRC) contains neurons that burst just before the phrenic nerve discharge (PND) and rebound after inspiration (pre-I neurons). These neurons, called parafacial respiratory group (pfRG), have been interpreted as a master inspiratory oscillator, an expiratory rhythm generator or simply as neonatal precursors of retrotrapezoid (RTN) chemoreceptor neurons. pfRG neurons have not been identified in adults, and their phenotype is unknown. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 54 publications
(126 reference statements)
3
89
1
8
Order By: Relevance
“…However, microinjection of KYN into BötC did not abolish the AbN response to chemoreflex activation. To explain why the AbN response to chemoreflex activation was not abolished after bilateral microinjections of KYN into the RVLM/BötC, we must take into account the findings by Fortuna et al (2008) showing that some RTN neurons send projections to the retroambiguus region, the site of premotor bulbospinal expiratory neurons. We observed that the average increase in the magnitude of tSN in response to chemoreflex activation was not affected by bilateral microinjections of KYN into the RVLM/pre-BötC.…”
Section: Discussionmentioning
confidence: 99%
“…However, microinjection of KYN into BötC did not abolish the AbN response to chemoreflex activation. To explain why the AbN response to chemoreflex activation was not abolished after bilateral microinjections of KYN into the RVLM/BötC, we must take into account the findings by Fortuna et al (2008) showing that some RTN neurons send projections to the retroambiguus region, the site of premotor bulbospinal expiratory neurons. We observed that the average increase in the magnitude of tSN in response to chemoreflex activation was not affected by bilateral microinjections of KYN into the RVLM/pre-BötC.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they might be Phox2b-ir cells. A recent study (Fortuna et al, 2008) reported that a population of rostral ventral respiratory neurons (i.e., glycinergic expiratory augmenting neurons) develops a preinspiratory discharge during hypercapnic hypoxia in adult rat in vivo preparations. Despite differences between experimental conditions, these results also support existence of heterogeneous subpopulations of Pre-I neurons in the rostral medulla around the caudal end of the facial nucleus.…”
Section: Characteristics Of Parafacial Neurons In the Ventral Medullamentioning
confidence: 99%
“…Motor activity during late (active) expiration emerges during forced breathing and involves active contraction of abdominal and thoracic expiratory muscle groups. The active or late phase of expiration is always present centrally, but in terms of the motor act of exhalation, it may be only activated during high metabolic demands (Fortuna et al 2008) or after experimental challenges involving intermittent hypoxia (Zoccal et al 2008). However, active expiration under physiological conditions is always preceded by post-I and thus, the alternating phases of inspiration and expiration are largely governed by central oscillations between inspiratory and post-I neurons.…”
Section: The Motor Pattern Of Breathingmentioning
confidence: 99%